Mitochondrial Haplogroups Define Two Phenotypes of Osteoarthritis - Fernandez-Moreno, Mercedes; Hermida-Soto, Angel; Oreiro, Natividad; Fernandez-Lopez, Carlos; Pertega, Sonia; Rego-Perez, Ignacio; Blanco, Francisco J (Frontiers in Physiology, 2012)
Objective. To assess a mitochondrion-related phenotype in patients with osteoarthritis (OA). Methods. Serum levels of the following OA-related biomarkers: matrix metalloproteinase-1 (MMP-1); MMP-3; MMP-13; myeloperoxidase (MPO); a peptide of the alpha-helical region of type II collagen, Coll2-1, and its nitrated form Coll2-1NO2; a C-terminal neoepitope generated by the collagenase-mediated cleavage of collagen type II triple helix, C2C; the C-propeptide of collagen type II, CPII; hyaluronic acid (HA); human cartilage glycoprotein-39, YKL-40; cartilage oligomeric matrix protein (COMP) and cathepsin K were analyzed in 48 OA patients and 52 healthy controls carrying the haplogroups H and J. Logistic regression models and Receiver Operating Characteristic (ROC) curves were performed to predict the onset of OA. Results. MMP-13 was the only biomarker significantly increased in OA patients compared to healthy controls in both haplogroups H and J. The collagen type II biomarkers, Coll2-1, Coll2-1NO2, the Coll2-1NO2/Coll2-1 ratio, C2C, CPII and the C2C:CPII ratio were significantly increased in OA patients carrying haplogroup H compared to OA carriers of the haplogroup J. Two logistic regression models for diagnosis were constructed and adjusted for age, gender and body mass index (BMI). For haplogroup H, the biomarkers significantly associated with OA were MMP-13 and Coll2-1; the area under the curve (AUC) of the ROC curve for this model was 0.952 (95%CI=0.892-1.012). For haplogroup J, the only biomarker significantly associated with OA was MMP-13; the AUC for this model was 0.895 (95%CI=0.801-0.989). Conclusion. Some OA-related biomarkers show a clearly different profile depending on the mtDNA haplogroup.